HUBUNGAN RELIGIUSITAS DAN KECENDERUNGAN POLA ASUH OTORITER DENGAN PERILAKU PROSOSIAL REMAJA DI PONDOK PESANTREN - Ellyana Ilsan Eka (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2013)
The purpose of this research is testing the relation between religiousness and foster pattern authoritarian with prosocial behavior of adolescents in pesantren. The subjects of this research are 119 teenagers, 14-17 years. This research uses quantitative method. The data collection method uses the scale of psychology are arranged based on variable construct theory of religiousness, authoritarian patterns and prosocial behavior. The data analysis used is regression and partial analysis. Research result indicates there is a relation between religiousness and the more authoritarian pattern with prosocial behavior (Freg = 0,7758; p = 0,001 0,05), and there is a negative relationship between the more authoritarian pattern with prosocial behavior (rpartial = - 0,395; treg = -3,644; p = 0,001